The age of migration : international population movements in the modern world - Castles, Stephen; Miller, Mark J. (Basingstoke [England] ; New York : Palgrave Macmillan, 2009)
This edition provides coverage of the nature, extent and dimensions of international population movements and of their consequences in an increasingly multicultural world.
Introduction -- Theories of migration -- Globalization, development and migration -- International migration before 1945 -- Migration to Europe, North America and Oceania since 1945 -- Migration in the Asia-Pacific region -- Migration in Sub-Saharan Africa, the Middle East and North Africa, and Latin America -- The state and international migration : the quest for control -- Migration and security -- Migrants and minorities in the labour force -- New ethnic minorities and society -- Migrants and politics -- Conclusion : migration and mobility in the twenty-first century.
Previous ed.: 2003.
Includes bibliographical references (p. 313-349) and indexes.
Keywords: Emigration and immigration; Emigration and immigration -- History; Migratie (demografie)